Trends in awareness and uptake of genetic testing among the United States population, 2011–2022 - Ariana Naaseh; Mengyao Shi; Steven Tohmasi; Erin L. Linnenbringer; Julie A. Margenthaler; Graham A. Colditz; Yin Cao (Journal of Community Genetics, 2026)
While genetic testing (GT) has become more available over the past decade, it is unclear whether public awareness and use have increased proportionally. We aimed to evaluate national trends in GT awareness and usage. We performed a cross-sectional analysis of nationally representative data from the National Cancer Institute’s Health Information National Trends Survey (HINTS). We analyzed survey responses from HINTS 4 Cycle 1–4 (2011–2014), 5 Cycle 1 and 4 (2017, 2020), and 6 (2022). Primary outcomes were overall genetic testing awareness and uptake. Secondary analyses evaluated awareness and uptake of health-related genetic testing (e.g. disease risk, cancer, and carrier testing) among survey cycles in which specific testing modalities were available. Linear regression assessed crude trends and multivariable logistic regression estimated odds ratios (OR). Among 22,256 respondents, overall awareness of GT increased from 36.6% in 2011 to 81.7% in 2022 (trend p < .001). Awareness was lower among individuals who were older (e.g., ref: age 18–34 , age 75+: OR 0.53 , 95% confidence interval [CI]: 0.43–0.64 ), male ( ref: female , OR 0.85 , CI: 0.77–0.95 ), non-Hispanic Black ( ref: non-Hispanic White , OR 0.63 , CI: 0.54–0.74 ), non-Hispanic Asian ( ref: non-Hispanic White , OR 0.38 , CI: 0.29–0.48 ), Hispanic ( ref: non-Hispanic White , OR 0.60 , CI: 0.52–0.69 ), with less than a college education (e.g., ref: some college , less than high school: OR 0.60 , CI: 0.47–0.77 ), and with annual household income <$75,000 (e.g., ref: >$75 , 000 , <$20 , 000: OR 0.49 , CI: 0.42–0.59 ). GT uptake increased from 21.4% in 2020 to 35.6% in 2022 (trend p < .001). GT uptake was lower among individuals who were non-Hispanic Asian ( ref: non-Hispanic White , OR 0.60 , CI: 0.38–0.96 ) and had household incomes <$35,000 (e.g., ref: >$75 , 000 , <$20 , 000: OR 0.68 , CI: 0.49–0.94 ), but higher among those with a personal history of cancer ( ref: no cancer history , OR 1.44 , CI: 1.07–1.92 ). Although GT awareness has grown, there are notable gaps across sociodemographic groups. Further study should better characterize factors influencing health-related GT uptake patterns.

Avoiding lead-time bias by estimating stage-specific proportions of cancer and non-cancer deaths - Ellen T. Chang; Christina A. Clarke; Graham A. Colditz; Allison W. Kurian; Earl Hubbell (Cancer Causes & Control, 2024)
Purpose Understanding how stage at cancer diagnosis influences cause of death, an endpoint that is not susceptible to lead-time bias, can inform population-level outcomes of cancer screening. Methods Using data from 17 US Surveillance, Epidemiology, and End Results registries for 1,154,515 persons aged 50–84 years at cancer diagnosis in 2006–2010, we evaluated proportional causes of death by cancer type and uniformly classified stage, following or extrapolating all patients until death through 2020. Results Most cancer patients diagnosed at stages I–II did not go on to die from their index cancer, whereas most patients diagnosed at stage IV did. For patients diagnosed with any cancer at stages I–II, an estimated 26% of deaths were due to the index cancer, 63% due to non-cancer causes, and 12% due to a subsequent primary (non-index) cancer. In contrast, for patients diagnosed with any stage IV cancer, 85% of deaths were attributed to the index cancer, with 13% non-cancer and 2% non-index-cancer deaths. Index cancer mortality from stages I–II cancer was proportionally lowest for thyroid, melanoma, uterus, prostate, and breast, and highest for pancreas, liver, esophagus, lung, and stomach. Conclusion Across all cancer types, the percentage of patients who went on to die from their cancer was over three times greater when the cancer was diagnosed at stage IV than stages I–II. As mortality patterns are not influenced by lead-time bias, these data suggest that earlier detection is likely to improve outcomes across cancer types, including those currently unscreened.

Pectoral muscle removal in mammogram images: A novel approach for improved accuracy and efficiency - Simin Chen; Debbie L. Bennett; Graham A. Colditz; Shu Jiang (Cancer Causes & Control, 2024)
Purpose Accurate pectoral muscle removal is critical in mammographic breast density estimation and many other computer-aided algorithms. We propose a novel approach to remove pectoral muscles form mediolateral oblique (MLO) view mammograms and compare accuracy and computational efficiency with existing method (Libra). Methods A pectoral muscle identification pipeline was developed. The image is first binarized to enhance contrast and then the Canny algorithm was applied for edge detection. Robust interpolation is used to smooth out the pectoral muscle region. Accuracy and computational speed of pectoral muscle identification was assessed using 951 women (1,902 MLO mammograms) from the Joanne Knight Breast Health Cohort at Washington University School of Medicine. Results Our proposed algorithm exhibits lower mean error of 12.22% in comparison to Libra’s estimated error of 20.44%. This 40% gain in accuracy was statistically significant ( p < 0.001). The computational time for the proposed algorithm is 5.4 times faster when compared to Libra (5.1 s for proposed vs. 27.7 s for Libra per mammogram). Conclusion We present a novel approach for pectoral muscle removal in mammogram images that demonstrates significant improvement in accuracy and efficiency compared to existing method. Our findings have important implications for the development of computer-aided systems and other automated tools in this field.

Repeated measures of mammographic density and texture to evaluate prediction and risk of breast cancer: a systematic review of the methods used in the literature - Akila Anandarajah; Yongzhen Chen; Carolyn Stoll; Angela Hardi; Shu Jiang; Graham A. Colditz (Cancer Causes & Control, 2023)
Purpose It may be important for women to have mammograms at different points in time to track changes in breast density, as fluctuations in breast density can affect breast cancer risk. This systematic review aimed to assess methods used to relate repeated mammographic images to breast cancer risk. Methods The databases including Medline (Ovid) 1946-, Embase.com 1947-, CINAHL Plus 1937-, Scopus 1823-, Cochrane Library (including CENTRAL), and Clinicaltrials.gov were searched through October 2021. Eligibility criteria included published articles in English describing the relationship of change in mammographic features with risk of breast cancer. Risk of bias was assessed using the Quality in Prognostic Studies tool. Results Twenty articles were included. The Breast Imaging Reporting and Data System and Cumulus were most commonly used for classifying mammographic density and automated assessment was used on more recent digital mammograms. Time between mammograms varied from 1 year to a median of 4.1, and only nine of the studies used more than two mammograms. Several studies showed that adding change of density or mammographic features improved model performance. Variation in risk of bias of studies was highest in prognostic factor measurement and study confounding. Conclusion This review provided an updated overview and revealed research gaps in assessment of the use of texture features, risk prediction, and AUC. We provide recommendations for future studies using repeated measure methods for mammogram images to improve risk classification and risk prediction for women to tailor screening and prevention strategies to level of risk.

Joanne Knight Breast Health Cohort at Siteman Cancer Center - Graham A. Colditz; Debbie L. Bennett; Jennifer Tappenden; Courtney Beers; Nicole Ackermann; Ningying Wu; Jingqin Luo; Sarah Humble; Erin Linnenbringer; Kia Davis; Shu Jiang; Adetunji T. Toriola (Cancer Causes & Control, 2022)
Purpose The Joanne Knight Breast Health Cohort was established to link breast cancer risk factors, mammographic breast density, benign breast biopsies and associated tissue markers, and blood markers in a diverse population of women undergoing routine mammographic screening to study risk factors and validate models for breast cancer risk prediction. Methods Women were recruited from November 2008 to April 2012 through the mammography service at the Joanne Knight Breast Health Center at Washington University in St. Louis, Missouri. Baseline questionnaire risk factors, blood, and screening mammograms were collected from 12,153 women. Of these, 1,672 were excluded for prior history of any cancer (except non-melanoma skin) or diagnosis of breast cancer within 6 months of blood draw/registration for the study, for a total of 10,481 women. Follow-up is through linking to electronic health records, tumor registry, and death register. Routine screening mammograms are collected every 1–2 years and incident benign breast biopsies and cancers are identified through record linkage to pathology and tumor registries. Formal fixed tissue samples are retrieved and stored for analysis. County-level measures of structural inequality were derived from publicly available resources. Results Cohort Composition: median age at entry was 54.8 years and 26.7% are African American. Through 2020, 74% of participants have had a medical center visit within the past year and 80% within the past 2 years representing an average of 9.7 person-years of follow-up from date of blood draw per participant. 9,997 women are continuing in follow-up. Data collected at baseline include breast cancer risk factors, plasma and white blood cells, and mammograms prior to baseline, at baseline, and during follow-up. Conclusion This cohort assembled and followed in a routine mammography screening and care setting that serves a diverse population of women in the St. Louis region now provides opportunities to integrate study of questionnaire measures, plasma and DNA markers, benign and malignant tissue markers, and repeated breast image features into prospective evaluation for breast cancer etiology and outcomes.

Commentary: 20 years online with “Your Disease Risk” - Graham A. Colditz; Hank Dart (Cancer Causes & Control, 2021)
The Your Disease Risk tool (yourdiseaserisk.wustl.edu) went live to the public in January 2000 and was one of the first personalized health risk assessment sites on the Internet. Its launch marked the culmination of years of work by a large, multi-disciplinary university team whose primary goal was to translate the science on cancer prevention into accurate, engaging, and useful messages for the public. Today, 20 years on, Your Disease Risk has expanded from its initial four cancers to include 18 different tools designed for today’s users. This commentary reviews important moments and lessons learned in the first two decades of Your Disease Risk.

Adolescent dairy product and calcium intake in relation to later prostate cancer risk and mortality in the NIH-AARP Diet and Health Study - Tuo Lan; Yikyung Park; Graham A. Colditz; Jingxia Liu; Molin Wang; Kana Wu; Edward Giovannucci; Siobhan Sutcliffe (Cancer Causes & Control, 2020)

Associations of aspirin and other anti-inflammatory medications with mammographic breast density and breast cancer risk - Lusine Yaghjyan; Akemi Wijayabahu; A. Heather Eliassen; Graham Colditz; Bernard Rosner; Rulla M. Tamimi (Cancer Causes & Control, 2020)

Do breast quadrants explain racial disparities in breast cancer outcomes? - Yunan Han; Justin Xavier Moore; Marvin Langston; Lindsay Fuzzell; Saira Khan; Marquita W. Lewis; Graham A. Colditz; Ying Liu (Cancer Causes & Control, 2019)

Childhood diet and growth in boys in relation to timing of puberty and adult height: the Longitudinal Studies of Child Health and Development - Aliya Alimujiang; Graham A. Colditz; Jane D. Gardner; Yikyung Park; Catherine S. Berkey; Siobhan Sutcliffe (Cancer Causes & Control, 2018)

Rural–urban differences in surgical treatment, regional lymph node examination, and survival in endometrial cancer patients - Whitney E. Zahnd; Katherine S. Hyon; Paula Diaz-Sylvester; Sonya R. Izadi; Graham A. Colditz; Laurent Brard (Cancer Causes & Control, 2018)

Pelvic inflammatory disease and the risk of ovarian cancer: a meta-analysis - Zhiyi Zhou; Fangfang Zeng; Jianhui Yuan; Jinling Tang; Graham A. Colditz; Shelley S. Tworoger; Britton Trabert; Xuefen Su (Cancer Causes & Control, 2017)

A Framework for Training Transdisciplinary Scholars in Cancer Prevention and Control - Aimee S. James; Sarah Gehlert; Deborah J. Bowen; Graham A. Colditz (Journal of Cancer Education, 2015)

Adolescent dietary vitamin D and sun exposure in relation to benign breast disease - Caroline E. Boeke; Rulla M. Tamimi; Catherine S. Berkey; Graham A. Colditz; Edward Giovannucci; Susan Malspeis; Walter C. Willett; A. Lindsay Frazier (Cancer Causes & Control, 2015)

Intakes of fat and micronutrients between ages 13 and 18 years and the incidence of proliferative benign breast disease - Xuefen Su; Caroline E. Boeke; Laura C. Collins; Heather J. Baer; Walter C. Willett; Stuart J. Schnitt; James L. Connolly; Bernard Rosner; Graham A. Colditz; Rulla M. Tamimi (Cancer Causes & Control, 2015)

Screening for colorectal cancer: using data to set prevention priorities - Graham A. Colditz; Lucy D’Agostino McGowan; Aimee S. James; Kari Bohlke; Melody S. Goodman (Cancer Causes & Control, 2014)

An institutional strategy to increase minority recruitment to therapeutic trials - Victoria V. Anwuri; Lannis E. Hall; Katherine Mathews; Brian C. Springer; Jennifer R. Tappenden; Dione M. Farria; Sherrill Jackson; Melody S. Goodman; Timothy J. Eberlein; Graham A. Colditz (Cancer Causes & Control, 2013)

Eight ways to stay healthy after cancer: an evidence-based message - Kathleen Y. Wolin; Hank Dart; Graham A. Colditz (Cancer Causes & Control, 2013)

Estrogen receptor positive tumors: Do reproductive factors explain differences in incidence between black and white women? - Erica T. Warner; Rulla M. Tamimi; Deborah A. Boggs; Bernard Rosner; Lynn Rosenberg; Graham A. Colditz; Julie R. Palmer (Cancer Causes & Control, 2013)

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

Mammographic breast density and breast cancer risk by menopausal status, postmenopausal hormone use and a family history of breast cancer - Lusine Yaghjyan; Graham A. Colditz; Bernard Rosner; Rulla M. Tamimi (Cancer Causes & Control, 2012)

Commentary: eight ways to prevent cancer: a framework for effective prevention messages for the public - Hank Dart; Kathleen Y. Wolin; Graham A. Colditz (Cancer Causes & Control, 2012)

Vitamin D and mammographic breast density: a systematic review - Lusine Yaghjyan; Graham A. Colditz; Bettina Drake (Cancer Causes & Control, 2012)

Transdisciplinary Training in Cancer Prevention: Reflections on Two Decades of Training - Graham A. Colditz; Kathleen Y. Wolin (Journal of Cancer Education, 2011)

Lifetime physical activity and the incidence of proliferative benign breast disease - Michelle M. Jung; Graham A. Colditz; Laura C. Collins; Stuart J. Schnitt; James L. Connolly; Rulla M. Tamimi (Cancer Causes & Control, 2011)

Estrogens in the breast tissue: a systematic review - Lusine Yaghjyan; Graham A. Colditz (Cancer Causes & Control, 2011)

Cohorts and consortia conference: a summary report (Banff, Canada, June 17–19, 2009) - Paolo Boffetta; Graham A. Colditz; John D. Potter; Laurence Kolonel; Paula J. Robson; Reza Malekzadeh; Daniela Seminara; Ellen L. Goode; Keun-Young Yoo; Paul Demers; Richard Gallagher; Ross Prentice; et al. (Cancer Causes & Control, 2011)

Overview of the Epidemiology Methods and Applications: Strengths and Limitations of Observational Study Designs - Graham A. Colditz (Critical Reviews in Food Science and Nutrition, 2010)

Pooled analyses of 13 prospective cohort studies on folate intake and colon cancer - Dong-Hyun Kim; Stephanie A. Smith-Warner; Donna Spiegelman; Shiaw-Shyuan Yaun; Graham A. Colditz; Jo L. Freudenheim; Edward Giovannucci; R. Alexandra Goldbohm; Saxon Graham; Lisa Harnack; Eric J. Jacobs; Michael Leitzmann; et al. (Cancer Causes & Control, 2010)

Intake of fiber and nuts during adolescence and incidence of proliferative benign breast disease - Xuefen Su; Rulla M. Tamimi; Laura C. Collins; Heather J. Baer; Eunyoung Cho; Laura Sampson; Walter C. Willett; Stuart J. Schnitt; James L. Connolly; Bernard A. Rosner; Graham A. Colditz (Cancer Causes & Control, 2010)

Ensuring long-term sustainability of existing cohorts remains the highest priority to inform cancer prevention and control - Graham A. Colditz (Cancer Causes & Control, 2010)

Physical activity and premenopausal breast cancer: an examination of recall and selection bias - Sonia S. Maruti; Walter C. Willett; Diane Feskanich; Beverly Levine; Bernard Rosner; Graham A. Colditz (Cancer Causes & Control, 2009)

Analysis of lung cancer incidence in the nurses’ health and the health professionals’ follow-up studies using a multistage carcinogenesis model - Rafael Meza; William D. Hazelton; Graham A. Colditz; Suresh H. Moolgavkar (Cancer Causes & Control, 2008)

Breastfeeding and risk of ovarian cancer in two prospective cohorts - Kim N. Danforth; Shelley S. Tworoger; Jonathan L. Hecht; Bernard A. Rosner; Graham A. Colditz; Susan E. Hankinson (Cancer Causes & Control, 2007)

Cohort studies of etiology and survival after cancer: the unique needs for uninterrupted funding - Graham A. Colditz (Cancer Causes & Control, 2007)

From epidemiology to cancer prevention: implications for the 21st Century - Graham A. Colditz (Cancer Causes & Control, 2007)

Manganese superoxide dismutase polymorphism and risk of skin cancer (United States) - Jiali Han; Graham A. Colditz; David J. Hunter (Cancer Causes & Control, 2007)

Frequent Tanning Bed Use, Weight Concerns, and Other Health Risk Behaviors in Adolescent Females (United States) - David L. O’Riordan; Alison E. Field; Alan C. Geller; Daniel R. Brooks; Gideon Aweh; Graham A. Colditz; A. Lindsay Frazier (Cancer Causes & Control, 2006)

A Pooled Analysis of 12 Cohort Studies of Dietary Fat, Cholesterol and Egg Intake and Ovarian Cancer - Jeanine M. Genkinger; David J. Hunter; Donna Spiegelman; Kristin E. Anderson; W. Lawrence Beeson; Julie E. Buring; Graham A. Colditz; Gary E. Fraser; Jo L. Freudenheim; R. Alexandra Goldbohm; Susan E. Hankinson; Karen L. Koenig; et al. (Cancer Causes & Control, 2006)

A Prospective Study of Body Mass Index, Hypertension, and Smoking and the Risk of Renal Cell Carcinoma (United States) - Keith T. Flaherty; Charles S. Fuchs; Graham A. Colditz; Meir J. Stampfer; Frank E. Speizer; Walter C. Willett; Gary C. Curhan (Cancer Causes & Control, 2005)

Cataract Extraction and Risk of Breast Cancer - Shumin M. Zhang; Walter C. Willett; Frank B. Hu; Edward L. Giovannucci; JoAnn E. Manson; Graham A. Colditz; Susan E. Hankinson (Cancer Causes & Control, 2004)

Estrogen Receptor β lpar;ESR2) Polymorphisms and Endometrial Cancer (United States) - Veronica Wendy Setiawan; Susan E. Hankinson; Graham A. Colditz; David J. Hunter; Immaculata De Vivo (Cancer Causes & Control, 2004)

Adolescent diet and risk of breast cancer - A. Lindsay Frazier; Lisa Li; Eunyong Cho; Walter C. Willett; Graham A. Colditz (Cancer Causes & Control, 2004)

A meta-analysis of asthma and risk of lung cancer (United States) - Alfredo A. Santillan; Carlos A. Camargo; Graham A. Colditz (Cancer Causes & Control, 2003)

Aspirin, other NSAIDs, and ovarian cancer risk (United States) - Kathleen M. Fairfield; David J. Hunter; Charles S. Fuchs; Graham A. Colditz; Susan E. Hankinson (Cancer Causes & Control, 2002)

Harvard Report on Cancer Prevention, Volume 5 Fulfilling the potential for cancer prevention: policy approaches - Graham A. Colditz; Michelle Samplin-Salgado; Catherine Tomeo Ryan; Hank Dart; Laurie Fisher; Angela Tokuda; Beverly Rockhill (Cancer Causes & Control, 2002)

Vitamins and carotenoids intake and the risk of basal cell carcinoma of the skin in women (United States) - Teresa T. Fung; David J. Hunter; Donna Spiegelman; Graham A. Colditz; Frank E. Speizer; Walter C. Willett (Cancer Causes & Control, 2002)

Prostate cancer screening practices and cancer control research (United States) - David Schottenfeld; Graham A. Colditz (Cancer Causes & Control, 2002)

Bowel movement, use of laxatives and risk of colorectal adenomatous polyps among women (United States) - Laurent Elizabeth A. Dukas; Graham A. Colditz; Walter C. Willett; Edward L. Giovannucci (Cancer Causes & Control, 2000)

Changing dietary patterns and cancer prevention: alpha-linolenic acid health risks and benefits - Graham A. Colditz (Cancer Causes & Control, 2000)

Proportion of colon cancer risk that might be preventable in a cohort of middle-aged US men - Elizabeth A. Platz; Walter C. Willett; Graham A. Colditz; Eric B. Rimm; Donna Spiegelman; Edward Giovannucci (Cancer Causes & Control, 2000)

Illnesses caused by smoking cigarettes - Graham A. Colditz (Cancer Causes & Control, 2000)

Tobacco industry advertising and adolescent smoking (United States) - Laurie Fisher; Graham A. Colditz (Cancer Causes & Control, 1999)

Year 2000 Cancer Mortality Falls in the United States Science Citation Index Rises for the Journal Cancer Causes and Control Increases Circulation - Graham A. Colditz (Cancer Causes & Control, 1999)

Glycosylated hemoglobin and risk of colorectal cancer and adenoma (United States) - Elizabeth A. Platz; Susan E. Hankinson; Nader Rifai; Graham A. Colditz; Frank E. Speizer; Edward Giovannucci (Cancer Causes & Control, 1999)

Screening endoscopy and risk of colorectal cancer in United States men - Charles S. Fuchs; Edward L. Giovannucci; Graham A. Colditz; Anne M. Kavanagh (Cancer Causes & Control, 1998)

Diabetes mellitus and risk of prostate cancer (United States) - Edward Giovannucci; Eric B. Rimm; Meir J. Stampfer; Graham A. Colditz; Walter C. Willett (Cancer Causes & Control, 1998)

Parity and other reproductive factors and risk of adenomatous polyps of the distal colorectum (United States) - Elizabeth A. Platz; Maria Elena Martinez; Francine Grodstein; Charles S. Fuchs; Graham A. Colditz; Meir J. Stampfer; Edward Giovannucci (Cancer Causes & Control, 1997)

Physical activity and reduced risk of colon cancer: implications for prevention - Graham A. Colditz; Carolyn C. Cannuscio; A. Lindsay Frazier (Cancer Causes & Control, 1997)

A prospective study of oral contraceptive use and risk of breast cancer (Nurses' Health Study, United States) - Susan E. Hankinson; Graham A. Colditz; JoAnn E. Manson; Walter C. Willett; David J. Hunter; Meir J. Stampfer; Frank E. Speizer (Cancer Causes & Control, 1997)